Fibrillarin methylates H2A in RNA polymerase I trans-active promoters in Brassica oleracea - Loza-Muller, Lloyd; Rodríguez-Corona, Ulises; Sobol, Margarita; Rodríguez-Zapata, Luis C.; Hozak, Pavel; Castano, Enrique (Frontiers in Plant Science, 2015)
Fibrillarin is a well conserved methyltransferase involved in several if not all of the more than 100 methylations sites in rRNA which are essential for proper ribosome function. It is mainly localized in the nucleoli and Cajal bodies inside the cell nucleus where it exerts most of its functions. In plants, fibrillarin binds directly the guide RNA together with Nop56, Nop58 and 15.5ka proteins to form a snoRNP complex that selects the sites to be methylated in pre-processing of ribosomal RNA. Recently, the yeast counterpart NOP1 was found to methylate histone H2A in the nucleolar regions. Here we show that plant fibrillarin can also methylate histone H2A. In Brassica floral meristem cells the methylated histone H2A is mainly localized in the nucleolus but unlike yeast or human cells it also localize in the periphery of the nucleus. In specialized transport cells the pattern is altered and it exhibits a more diffuse staining in the nucleus for methylated histone H2A as well as for fibrillarin. Here we also show that plant fibrillarin is capable of interacting with H2A and carry out its methylation in the rDNA promoter.